Enhancing thermomechanical and chemical stability of polymer electrolyte membranes using polydopamine coated nanocellulose - Ram, Farsa; Velayutham, Parthiban; Sahu, Akhila Kumar; Lele, Ashish K.; Shanmuganathan, Kadhiravan (ACS Applied Energy Materials, 2020)
We report here an approach to enhance the chemical and thermomechanical stability of polymer electrolyte membranes without compromising proton conductivity. Multifunctional polydopamine coated nanocellulose (PNC) was prepared by oxidative polymerization of dopamine on nano cellulose fibers and subsequently incorporated in Nafion by solution blending. PNC had a very significant effect on the thermomechanical properties of Nafion showing up to 200% improvement in the storage modulus at 90 degrees C. The PNC network also enhanced the dimensional stability of Nafion under constant stress. The 3 wt % PNC composite membrane showed a drastic reduction in creep compliance of about 39.9% and 46.5% in J(max) at 30 degrees and 60 degrees C, respectively. Free radical scavenging properties of polydopamine also helped to significantly enhance the chemical stability of Nafion, which was ascertained by accelerated degradation tests conducted in Fenton's reagent at 70 degrees C over 40 days. F-19 CP MAS solid state NMR, FTIR, and tensile tests on the membranes show higher chemical stability of the 3 wt % PNC composite membrane. The proton conductivity of the 3 wt % PNC composite membrane at 90 degrees C and 100% RH (similar to 125 mS/cm) was slightly higher than the Nafion membrane (similar to 94 mS/cm) at similar conditions. The retention of proton conductivity even with lower water uptake could be ascribed to proton hopping through polydopamine coated nanocellulose. Performance of the composite membrane was also evaluated in a single stack fuel cell and found to be better than recast Nafion. The benefits derived by this approach are not restricted to Nafion alone and shall broadly apply to many other polymer membranes.
Keywords: cellulose nanofibers; chemical stability; dimensional stability; fuel cell; polydopamine; polymer electrolyte membrane